MICROSTRUCTURAL CHARACTERIZATION OF DUAL AND MULTIPHASE STEELS APPLIED TO AUTOMOTIVE INDUSTRY - Fukugauchi, Cristina Sayuri [UNESP]; Faria Neto, Antonio dos Reis [UNESP]; Ribeiro, Rosinei Batista [UNESP]; Pereira, Marcelo dos Santos [UNESP]; Hotza, D. (Trans Tech Publications Ltd, 2014)
TRIP (Transformation Induced Plasticity) and DP (Dual-Phase) steels are written in a new series of steels which present excellent mechanical properties. As for microstructure aspect, TRIP steels consist on a ferrite matrix with a second phase dispersion of other constituents, such as bainite, martensite and retained austenite, while dual-phase steels consist on martensite dispersion in a ferrite matrix. In order to identify the different microconstituents present in these materials, microstructure characterization techniques by optical microscopy (using different etchants: LePera, Heat-Tinting and Nital) and scanning electron microscopy were carried out. This being so, microstructures were correlated with mechanical properties of materials, determined by means of tensile tests. It is concluded that steels assisted by TRIP effect have a strength and elongation relation higher than the dual-phase one. With microstructure characterization, it was observed phases present in these materials microstructure.
Keywords: Advanced steels; Microstructure characterization; Mechanical properties; LePera; Heat tinting